In vivo PSC differentiation as a platform to identify factors for improving the engraftability of cultured muscle stem cells - Xie, Ning; Robinson, Kathryn; Sundquist, Timothy; Chan, Sunny S. K. (Frontiers in Cell and Developmental Biology, 2024)
Producing an adequate number of muscle stem cells (MuSCs) with robust regenerative potential is essential for the successful cell therapy of muscle-wasting disorders. We have recently developed a method to produce skeletal myogenic cells with exceptional engraftability and expandability through an in vivo pluripotent stem cell (PSC) differentiation approach. We have subsequently mapped engraftment and gene expression and found that leukemia inhibitory factor receptor (Lifr) expression is positively correlated with engraftability. We therefore investigated the effect of LIF, the endogenous ligand of LIFR, on cultured MuSCs and examined their engraftment potential. We found that LIF-treated MuSCs exhibited elevated expression of PAX7, formed larger colonies from single cells, and favored the retention of PAX7+ “reserve cells” upon myogenic differentiation. This suggested that LIF promoted the maintenance of cultured MuSCs at a stem cell stage. Moreover, LIF enhanced the engraftment capability of MuSCs that had been expanded in vitro for 12 days by 5-fold and increased the number of MuSCs that repopulated the stem cell pool post-transplantation. These results thereby demonstrated the effectiveness of our in vivo PSC differentiation platform to identify positive regulators of the engraftability of cultured MuSCs.